HUBUNGAN FASILITAS BELAJAR DAN PERHATIAN ORANG TUA DI RUMAH DENGAN HASIL BELAJAR BIOLOGI SISWA SMAN 1 DANAU KEMBAR KABUPATEN SOLOK - Syofianti, Syofianti; Helendra, Helendra; Yulia Sari, Liza (STKIP PGRI Sumbar, 2014)
ABSTRACT This research is motivated by the lack of student learning facilities at home , causing the outcomes students biology learning became low. In addition, parents also rarely pay attention to their learning activities at home , so there are students who do not make the task of repeating the lessons at home and well . The purpose of this study is to examine : the relationship of learning facilities and caring parents at home together on Biology learning outcomesof student at SMAN 1Twin Lakes Solok district. This type of research is descriptive correlational. The population in this study were all students of class X Science and XI Science SMAN 1 Twin Lakes Solok district . Sampling technique in this study is the total sampling that members of the sampled population . Data learning facilities at home and parental concern was obtained from questionnaires , while data from subjects studied biology the value of a mid 1st semester of academic year 2013/2014 were obtained from the teacher . Analysis of the data in this study using the formula product Moment Correlation technique and to test the significance of the correlation coefficient r, can be tested by using the formula t . From the analysis of the data obtained ( 1 ) learning facility at home significantly related to the learning biology outcomes, ( 2 ) significant parental concern related to the biology learning outcomes and ( 3 ) learning facilities and attentive parents are jointly significantly associated with learning biology outcomes